Peran Supervisi Kepala Sekolah Terhadap Tugas Pokok Guru di SMA Negeri 1 Terara: Penelitian Tindak Sekolah Tahun Pelajaran 2022/2023 - Samsul Mujtahid (Literasi: Jurnal Pendidikan Guru Indonesia, 2023)
This study intends to reveal the problem of the teacher's main tasks objectively regarding "The Role of Supervision of the Principal in the Main Tasks of Teachers in SMA Negeri 1 Terara: Follow-Up Research for the 2022/2023 Academic Year." The purpose of this study is to reveal the supervisory role of the principal in the main tasks of the teacher in planning lessons, studying lesson plans, and implementing lessons. This study uses descriptive qualitative research. The data subjects in this study were 6 (six) teachers of SMA Negeri 1 Terara. Methodologically data was collected using an observation sheet (Observation). Based on the results of the data analysis that has been carried out in the Supervision Role of the Principal on the Main Tasks of the Teacher, it can be concluded that showing the initial conditions of 6 (six) teachers in the observation cycle I was proven by the low results of the average score achieved by the teachers from the three aspects observed, namely 54.5. Then, after conducting individual coaching to 6 (six) teachers. The results of the appointment in cycle II proved to be an increase by achieving a score of 86.3. Judging from the average value of cycle I to cycle II there was an increase in preparing lesson plans, reviewing lesson plans, and learning implementation of the six teachers of SMA Negeri 1 Terara as research subjects.